Subpopulations of liver coated vesicles resolved by preparative agarose gel electrophoresis (The Rockefeller University Press, 1986)
Rat liver clathrin coated vesicles (CVs) were separated into several distinct subpopulations using non-sieving concentrations of agarose, which allowed the separation of species differing primarily in surface charge. Using preparative agarose electrophoresis (Kedersha, N. L., and L. H. Rome, 1986, Anal. Biochem., in press), the CVs were recovered and analyzed for differences in morphology, coat protein composition, and stripped vesicle protein composition. Coat proteins from different populations appeared identical on SDS PAGE, and triskelions stripped from the different populations showed the same mobility on the agarose gel, suggesting that the mobility differences observed in intact CVs were due to differences in the surface charge of underlying vesicles rather than to variations in their clathrin coats. Several non-coat polypeptides appeared to segregate exclusively with different populations as resolved by two-dimensional electrophoresis. Stripped CVs also exhibited considerable heterogeneity when analyzed by Western blotting: the fast-migrating population was enriched in the mannose 6- phosphate receptor, secretory acetylcholine esterase, and an Mr 195,000 glycoprotein. The slow-migrating population of CVs was enriched in the asialoglycoprotein receptor, and it appeared to contain all detectable concanavalin A-binding polypeptides as well as the bulk of detectable WGA-binding proteins. When CVs were prepared from 125I- asialoorosomucoid-perfused rat liver, ligand was found in the slow- migrating CVs, suggesting that these were endocytic in origin. Morphological differences were also observed: the fast-migrating population was enriched in smaller CVs, whereas the slow-migrating population exhibited an enrichment in larger CVs. As liver consists largely of hepatocytes, these subpopulations appear to originate from the same cell type and probably represent CVs of different intracellular origin and destination.